The Impact of Intellectual Assets, Islamic Sustainability Reporting, and Green Performance on Sharia-Based Corporate Value - Yuni Mayanti; Iwan Setiawan; Setia Mulyawan (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
This study examines the impact of intellectual assets, Islamic sustainability reporting, and green performance on the corporate value of firms listed on the Jakarta Islamic Index (JII), with a particular focus on their alignment with Sharia principles. As key contributors to national economic growth, these firms face increasing competition that necessitates value creation grounded in ethical and sustainable practices. Employing a quantitative approach, this research utilizes purposive sampling to select 10 companies from a population of 30 Sharia-compliant firms. Data were analyzed using panel data regression with E-Views 12 software. The results reveal that individually, intellectual assets, Islamic sustainability reporting, and green performance do not significantly influence corporate value; however, collectively, these factors exert a significant and positive effect. This underscores the importance of integrating intangible resources with Sharia-based sustainability and environmental responsibility to enhance corporate valuation. The study highlights how adherence to maqāṣid al-sharī‘ah—particularly the preservation of wealth, life, and environment—can inform corporate strategies in Islamic capital markets. The findings provide empirical insights and a robust regression model useful for investors, regulators, and managers aiming to align financial performance with Sharia economic objectives.Keywords: Intellectual Assets; Islamic Sustainability Reporting; Green Performance; Corporate Value; Sharia Economics